Shifts in Fecal Metabolite Profiles Associated With Ramadan Fasting Among Chinese and Pakistani Individuals - Chen, Siyu; Ali, Ikram; Li, Xin; Long, Danfeng; Zhang, Ying; Long, Ruijun; Huang, Xiaodan (Frontiers in Nutrition, 2022)
The human gut microbiota has been proposed to serve as a multi-functional organ in host metabolism, contributing effects to nutrient acquisition, immune response, and digestive health. Fasting during Ramadan may alter the composition of gut microbiota through changes in dietary behavior, which ultimately affects the contents of various metabolites in the gut. Here, we used liquid chromatography mass spectrometry-based metabolomics to investigate the composition of fecal metabolites in Chinese and Pakistani individuals before and after Ramadan fasting. Principal Component Analysis showed distinct separation of metabolite profiles among ethnic groups as well as between pre- and post-fasting samples. After Ramadan fasting, the Chinese and Pakistani groups showed significant differences in their respective contents of various fecal metabolites, In particular, L-Histidine, Lycofawcine and Cordycepin concentrations were higher after Ramadan fasting in the Chinese group, while Brucine was enriched in the Pakistani group. KEGG analysis suggested that metabolites related to Purine metabolism, 2 Oxocarboxylic acid metabolism, and Lysine degradation were significantly enriched in the total subject population pre-fasting vs post-fasting comparisons. Several bacterial taxa were significantly correlated with specific metabolites unique to each ethnic group, suggesting that changes in fecal metabolite profiles related to Ramadan fasting may be influenced by associated shifts in gut microbiota. The fasting-related differences in fecal metabolite profile, together with these group-specific correlations between taxa and metabolites, support our previous findings that ethnic differences in dietary composition also drive variation in gut microbial composition and diversity. This landscape view of interconnected dietary behaviors, microbiota, and metabolites contributes to future development of personalized, diet-based therapeutic strategies for gut-related disorders.